The relationship between anxiety and reading comprehension among Iranian UTM students - Keshavarz, Soolmaz (2011)
This investigation intended to find out the relationship between anxiety and reading comprehension. The subjects included forty-five postgraduate students who took the Intensive English Course (IEC) in UTM. The participants were asked to read texts, one in Persian and the other in English, in order to investigate the relationship between anxiety and reading comprehension while reading L1 and L2 texts. Anxiety questionnaires were used as the research instruments to identify the different levels of anxiety among three groups of learners successful, moderately successful, and less successful. The data were collected and analyzed through Pearson correlation and ANOVA. Results from the data analysis showed that the relation between reading and anxiety scores in L2 and L1 was negative, in which both first and second hypotheses were approved. It means that when the reading score was high the anxiety score was low and vice versa. In addition, the comparing means between groups for both L1 and L2 showed that the anxiety between groups was different. In other words, anxiety significantly differs between the three groups (successful, moderately successful, and less successful) in L1 and L2; therefore the third hypothesis was approved. As a recommendation, the researcher believes that the EFL reading instructors could help students comprehend a reading text better. In order to achieve this, they should have a good relationship with their students, provide a relax atmosphere, and give them some advice to cope with their anxiety.